Heart failure hospitalization in women with signs and symptoms of ischemia: A report from the women's ischemia syndrome evaluation study. (15th November 2016) - Bakir, May; Nelson, Michael D.; Jones, Erika; Li, Quanlin; Wei, Janet; Sharif, Behzad; Minissian, Margo; Shufelt, Chrisandra; Sopko, George; Pepine, Carl J.; Merz, C. Noel Bairey
Abstract: Background: Women with signs and symptoms of ischemia, no obstructive coronary artery disease, and preserved left ventricular ejection fraction enrolled in the National Heart Lung and Blood Institute (NHLBI) sponsored Women's Ischemia Syndrome Evaluation (WISE) study have an unexpectedly high rate of subsequent heart failure (HF) hospitalization. We sought to verify and characterize the HF hospitalizations. Methods: A retrospective chart review was performed on 223 women with signs and symptoms of ischemia, undergoing coronary angiography for suspected coronary artery disease followed for 6 ± 2.6 years. Data were collected from a single site in the WISE study. Results: At the time of study enrollment, the women were 57 ± 11 years of age, all had preserved left ventricular ejection fraction, and 81 (36%) had obstructive CAD (defined as > 50% stenosis in at least one epicardial artery). Among the 223 patients, 25 (11%) reported HF hospitalizations, of which 14/25 (56%) had recurrent HF hospitalizations (> 2 hospitalizations). Medical records were available in 13/25 (52%) women. Left ventricular ejection fraction was measured in all verified cases and was found to be preserved in 12/13 (92%). HF hospitalization was not related to obstructive CAD. Conclusion: Among women with signs and symptoms of ischemia undergoing coronary angiography for suspected obstructive CAD, HF hospitalization at 6-year follow-up was predominantly characterized by a preserved ejection fraction and not associated with obstructive CAD.